Hepatocellular carcinoma treated with sorafenib: Arterial tumor perfusion in dynamic contrast-enhanced CT as early imaging biomarkers for survival. Issue 98 (January 2018) - Nakamura, Yuko; Kawaoka, Tomokazu; Higaki, Toru; Fukumoto, Wataru; Honda, Yukiko; Iida, Makoto; Fujioka, Chikako; Kiguchi, Masao; Aikata, Hiroshi; Chayama, Kazuaki; Awai, Kazuo
Highlights: Pre-APtumor can identify patients who may benefit from sorafenib treatment. HCC perfusion was changed only one week after sorafenib administration. The APtumor ratio may be an early imaging biomarker. Abstract: Objectives: To investigate whether hepatic perfusion CT yields early imaging biomarkers predictive of the prognosis of hepatocellular carcinoma (HCC) patients treated with sorafenib. Methods: We evaluated 36 HCC patients who underwent hepatic perfusion CT before- and one week after sorafenib therapy. We measured arterial and portal perfusion in the hepatic tumor and liver parenchyma [(AP)(PP)tumor ], [(AP)(PP)liver ]. The perfusion ratio was calculated by dividing the post- by the pre-sorafenib value. The effect of each value on the overall survival rate was analyzed with the Cox proportional hazards model; statistically significant parameters were subjected to receiver operating characteristic analysis based on median survival after sorafenib administration to determine the overall survival rate with the Kaplan-Meier method. Results: Pre-APtumor was significantly associated with the overall survival rate (hazard ratio (HR) and 95% confidence interval (CI), 0.16 and 0.02-0.84, p = 0.03). The APtumor ratio tended to be associated with the overall survival rate (HR and 95% CI, 2.94 and 0.94-7.88, p = 0.06). The overall survival rate was higher in patients with pre-APtumor  > 71.7 mL/min/100 mL, and with APtumor ratio ≦ 1.1 (p < 0.01 and 0.03, respectively, in Kaplan-Meier method with log-rank). Conclusion: Hepatic perfusion CT yields early imaging biomarkers for predicting overall survival in HCC patients treated with sorafenib.